Resolving the mystery—How TCR transgenic mouse models shed light on the elusive case of gamma delta T cells - Hahn, Anne Maria; Winkler, Thomas (Journal of Leukocyte Biology, 2020)
Cutting-edge questions in αβ T cell biology were addressed by investigating a range of different genetically modified mouse models. In comparison, the γδ T cell field lacks behind on the availability of such models. Nevertheless, transgenic mouse models proved useful for the investigation of γδ T cell biology and their stepwise development in the thymus. In general, animal models and especially mouse models give access to a wide range of opportunities of modulating γδ T cells, which is unachievable in human beings. Because of their complex biology and specific tissue tropism, it is especially challenging to investigate γδ T cells in in vitro experiments since they might not reliably reflect their behavior and phenotype under physiologic conditions. This review aims to provide a comprehensive historical overview about how different transgenic mouse models contributed in regards of the understanding of γδ T cell biology, whereby a special focus is set on studies including the elusive role of the γδTCR. Furthermore, evolutionary and translational remarks are discussed under the aspect of future implications for the field. The ultimate full understanding of γδ T cells will pave the way for their usage as a powerful new tool in immunotherapy.
CRIS-Team Scopus Importer:2020-02-28
Keywords: gamma/delta T cells; transgenic mice